Peningkatan Perilaku Disiplin Anak Melalui Metode Pembiasaan di Taman Kanak-kanak Islam Terpadu Insan Kamil kelompok B1 usia 5-6 tahun - La Jaga, Rumiati; Arifin, Andi Agustan (JAPRA (Jurnal Pendidikan Raudhatul Athfal), 2019)
The purpose of this study is to know the method of habituation can improve the behavior of children's discipline in Kindergarten IT Insan Kamil Group B1. This research is a Classroom Action Research (PTK). Research subjects were 19 people. The design stage of the study includes planning, action or implementation, observation and reflection Technique of collecting data used is observation.The results obtained that the application of methods of habituation can improve the behavior of children's discipline in Kansan Integrated Islamic Kindergarten in Group B1 of South Halmahera Regency. In the first cycle of the observation results showed that the average of 20% of the ability of children has not developed and 43,5% of the ability of children began to develop while in cycle II there is an increase, the ability of children to develop as expectations of 56,27% and 26,75% very good growth.